Decolonization and Canada’s ‘Idle No More’ Movement - Li Xiu Woo, Grace (Arctic Review on Law and Politics, 2013)
Canada’s ‘Idle No More’ movement ignited over concern about Prime Minister Stephen Harper’s abuse of majority status to enact laws that undermine democratic rights and environmental protection. With a philosophy that corresponds to international human rights principles, the movement galvanized public opinion and forged stronger alliances with the settler population. Ironically, Indigenous peoples are currently better situated than Canadians to challenge the lack of public consultation and violation of democratic principles that have come to light. The Supreme Court of Canada has recently confirmed that there is a duty to consult aboriginal peoples on issues that affect their rights, and several court actions have now been mounted on this basis. The goal of correcting endemic injustices and reinvigorating democracy will require a full re-evaluation of Canada’s colonial past and of the institutional format used to dispossess Indigenous peoples. Idle No More’s iconic flash-mob round dances suggest there is a new generation ready to take on this challenge.Keywords: British colonialism, monarchy, democracy, Indigenous, law, rights, sovereigntyCitation: Arctic Review on Law and Politics, vol. 4, 2/2013 pp. 181–206. ISSN 1891-6252